Key Drivers In Stock Growth Of "Big Tobacco" - Fitchet, Max (School of Economics, 2019)
This study attempts to determine some of the key drivers in stock growth of BAT, IMB, JTI and PMI (“Big Tobacco”) which have seen strong growth in stock pricing from 2000 to 2016. The study uses a combination of financial statements and market related metrics to determine key trends. The results show that “Big Tobacco” has increased its share in the global market through acquisitions and diversification into the vaping and logistics markets. Share buy backs and increased margins have helped offset the decrease in cigarette consumption and have encouraged a bullish view of the industry. However, increasing dividend pay-out ratios, a falling cash conversion cycle and an increased tax burden suggest future difficulties. The market continues to price growth into “Big Tobacco” stocks, and while risk is low in the industry the same level of growth cannot be expected in the future without some changes in the sector. Further consolidation of the industry could provide more opportunity for investors.